Investigation of optical and structural properties of ion-assisted deposition (IAD) ZrO2 thin films - Farhan, M.S.; Zalnezhad, E.; Bushroa, A.R. (Springer Verlag (Germany), 2013)
Zirconium dioxide thin films were deposited onto fused silica glass substrates by electron-beam assisted by oxygen ions using high vacuum coater equipped with electron beam gun at ambient substrate temperature. The properties of the films have been investigated using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), micro-hardness testing, laser induced damage threshold (LIDT) and optical analysis. It is found that the crystalline phase is strongly influenced by ion energy and current density and an amorphous to monoclinic transition is occurred. The changes in crystallinity resulted in increase in the film micro-hardness up to19GPa, revealed in minimum residual stress -2GPa. LIDT increased up to 19 J/cm2 and the optical refractive index improved up to 2.23 at 550 nm wavelength for films deposited at ion energy of 400eV and 100μA/cm2 current density.